Exploring novel ligands with strong electron delocalization for high-performance blue CsPbBr3 perovskite nanoplatelets. Issue 26 (23rd June 2022) - Wen, Zhuoqi; Cui, Zhongjie; He, Haiyang; Yang, Dan; Mei, Shiliang; Yang, Bobo; Xiong, Zhiyong; Song, Shanliang; Bao, Rui; Zhang, Wanlu; Xing, Guichuan; Xie, Fengxian; et al.
Abstract : Lewis bases with strong electron delocalization can affect the chemical equilibrium of the system. Therefore, the R-NH3 +  and R–C≡C–COO −  prefer to coordinate with NPLs, passivating the surface defects and improving the stability of crystals. Abstract : Colloidal CsPbBr3 perovskite nanoplatelets (NPLs) with readily controllable thickness are considered promising blue-emitting materials. However, the relatively low photoluminescence quantum yield (PLQY) and poor stability hinder their further applications. Herein, a class of novel surface ligands, such as 2-butynoic acid (BtA), phenylpropiolic acid (PA) and 2-pentynoic acid (PtA), are proposed for conveniently preparing high-performance blue-emitting NPLs. Benefiting from the strong electron delocalization effect of alkynyl, the protonated amine species (RNH3 + ) and R–CC–COO − prefer to coordinate with the perovskite, which can not only enhance the PLQY of NPLs from ∼15% to ∼100%, but also promote their endurability to high temperatures and strong UV irradiation. To our knowledge, this is the first report on the post-treatment of perovskites with electron delocalized ligands containing alkynyl and the effect of electron delocalization of Lewis bases on high-performance NPLs is systematically investigated from the perspective of molecular structure, which will be helpful to develop novel short-chain and conjugated ligands for perovskite electroluminescence devices.